Pelanggaran Standar Operasional Prosedur Produksi Teh Iroet - Fisabilillah, Al Fattaah Muhammad Syah; Trimo, Lucyana (Jurnal Agro Industri Perkebunan, 2018)
Iroet Tea is a dry tea trademark owned by Koperasi Serba Usaha (KSU) Putera Mekar. Iroet tea products have been certified UTZ number two in the world and number one in Indonesia related to good plantation practices, good tea processing, environmental social issues, food safety, and quality improvement. Iroet Tea earned UTZ certificates in 2011 and 2013, but currently does not receive the certification, because there are many violations of the standard production procedures, so please note what violations that occur during the production process. The research design used in this research is qualitative with case study technique. The method used in this research is descriptive qualitative. KSU Putera Mekar has set the standard opertaion procedure since the process of picking shoots until dry tea processing process, so that if farmers and workers follow the standard procedure, then Iroet tea products produced will be good quality and get UTZ certificate. But many violations Iroet tea standard operation  procedures, from picking tea shoots, shoots at the shelter collecting the results, to the processing of dried tea is done at the factory. The results showed that there were many violations during the process of supplying raw materials to the production process, the violations committed in the form of non compliance with standard operation procedures and agreements related to raw materials needed, the process of gathering raw materials, and processing of dry tea.   Keywords: production, quality control, standard operation procedure, tea